Uncovering the local potential of the islands: Development of a reference book on popular plants of north Maluku with high economic value as teaching material for basic biology courses - Haerullah, Ade; Hasan, Said; Suparman, Suparman; Nasichah, Arini Z; Ahmad, Iswadi M. (Edelweiss Applied Science and Technology, 2025)
The rich biodiversity of the North Maluku Islands, particularly its economically valuable plant species, remains underutilized as educational material in biology instruction. This study aims to develop a reference book featuring popular economically significant plants of the North Maluku Islands for use in introductory biology courses. Employing a research and development (R&D) approach, the study integrates surveys and the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The survey involved interviews with 300 local residents, field observations, and literature reviews to identify popular plants and their economic and biological characteristics. Key species identified include nutmeg (Myristica fragrans), clove (Syzygium aromaticum), kenari (Canarium indicum), coconut (Cocos nucifera), sago (Metroxylon sp.), and durian (Durio zibethinus). The reference book was developed based on these findings and validated by subject-matter experts and media specialists. Results from the limited trial involving biology students at Khairun University indicated high levels of validity, practicality, and effectiveness. The contextually rich and locally grounded content of the book significantly enhanced students' comprehension of core biological concepts, demonstrating the value of integrating local natural resources into higher education biology curricula.